1993
DOI: 10.1111/j.1600-0722.1993.tb01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical bone mineral density in the mandible and osteoporosis status in postmenopausal women

Abstract: Kletnetti E, Vainio P, Lassila V, Alhava E: Cortical bone tnltteral density in the mandible and osteoporosis status in postmenopausal women. Scand J Dent Res 1993: 101: 219-23. © Munksgaard, 1993 Mineral density of the cortical bone of the mandible was determined by singleenergy QCT (quantitative computed tomography) for 77 menopausal women. Bone mineral densities (BMD) were measured in the buccal and lingual layers of the cortex, distally from the foramen mentale, on both sides of the mandible. All the women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
1
19

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 18 publications
4
80
1
19
Order By: Relevance
“…The second used method in this study is quantitative computed tomography (QCT) that allows for separate measurement of volumetric bone mineral density of the trabecular and cortical bone compartments (expressed in g/cm 3 ) as well as determination of mean volumetric tooth mineral density (TvBMD) and total tooth volume (Tvol). In contrast to DEXA, QCT eliminates the error in mineral density measurements present in the former method [4,8,10,15]. However, the resolution for miniature samples analysis is too small to provide precise results and relatively high doses of X-rays are emitted during the scanning procedure, which might not be particularly beneficial for living subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The second used method in this study is quantitative computed tomography (QCT) that allows for separate measurement of volumetric bone mineral density of the trabecular and cortical bone compartments (expressed in g/cm 3 ) as well as determination of mean volumetric tooth mineral density (TvBMD) and total tooth volume (Tvol). In contrast to DEXA, QCT eliminates the error in mineral density measurements present in the former method [4,8,10,15]. However, the resolution for miniature samples analysis is too small to provide precise results and relatively high doses of X-rays are emitted during the scanning procedure, which might not be particularly beneficial for living subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the large sample size of 263 jaw specimens it was economically not possible to study systemic bone disorders such as osteopenia and osteoporosis by means of x-rays or DEXA. Several studies reported that osteoporosis might promote ridge resorption (Bays & Weinstein, 1982;Kribbs et al, 1983;Hirai et al, 1993) (Klemetti et al 1993a;Klemetti et al 1993b;Bollen et al, 2004). Devlin & Horner (2007) state that age-related bone loss of the jaw resulting in cortical porosity and a reduced BMD and BMC (Hildebolt, 1997) has to be clearly distinguished from external alterations of the mandibular alveolar process due to tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…Klemetti (1994) 16 classified morphology of mandibular inferior cortex (MIC) by observing the mandible distally from mental foramen as follows:…”
Section: Morphology Of Mandibular Inferior Cortex (Mic)mentioning
confidence: 99%